Shear Bond Strength of Self-Adhering Flowable Composite on Dentin with and without Application of an Adhesive System. Issue 2 (May 2014) - Tuloglu, Nuray; Tunc, Emine Sen; Ozer, Sezin; Bayrak, Sule
Purpose: The aim of this study was to evaluate the shear bond strength (SBS) of conventional and self-adhering flowable resin composites on the dentin surfaces of primary and permanent teeth and to evaluate the effect of the application of an adhesive system under self-adhering flowable resin composite on SBS. Methods: Prepared permanent and primary tooth dentin surfaces were randomly distributed into 3 groups according to application protocols as follows: group 1: Vertise Flow; group 2: OptiBond + Filtek Ultimate; and group 3: OptiBond + Vertise Flow. A universal testing machine was used to measure SBS of prepared specimens, and data were analyzed using 1-way ANOVA and Tukey test. Results: Statistically significant differences were observed among all groups for primary and permanent teeth (P<0.05). The highest values were observed in group 2, followed by group 3, in both permanent and primary teeth. SBSs of all groups were significantly higher for permanent teeth than for primary teeth (P<0.05). Conclusion: Although SBS values of Vertise Flow groups were lower than those for conventional flowable resin composite groups, with further developments in material technology, self-adhering materials could be promising materials especially for pediatric dentistry.